PENGARUH PENERAPAN STRATEGI EXAMPLE NON EXAMPLE BERBASIS MEDIA KONKRET TERHADAP HASIL BELAJAR IPA - Nurjannah, Nurjannah; Safei, Safei; Rosdiana, Rosdiana; Basam, Fajri (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
The purpose of this study where: 1) To describe the science learning outcomes before applying the concrete media-based example non example strategy to the fourth grade at SDN 017 Bonra Kab.Polman. 2) To describe the learning outcomes after applying the concrete media-based example non-example strategy to the fourth grade at SDN 017 Bonra Kab.Polman. 3) To find out the effect of the application of the example non example strategy based on concrete media affect the science learning outcomes of SDN 017 Bonra Kab. Polman. This study uses a quantitative approach with a pre-experimental design and a one-group pretest-posttest research design. The population in this study were all students of four grade class SDN 017 Bonra, totaling 18 people. The sampling technique used was the saturated sample technique. The instruments used in this research were tests and documentation. Data analysis techniques used were descriptive statistics and inferential statistics. Based on the results of research using descriptive statistics, the average value before the implementation of the concrete media-based example non example strategy was 31.39 and the average value after the concrete media-based example non-example strategy was 81.39. The results of inferential statistical analysis obtained the value of tcount = 23,805 and the value of ttable = 1,739, then tcount> ttable, which is 23,805> 1,739. It can be said that there was an effect of implementing an example non example strategy based on concrete media on student learning outcomes in science subjects in class IV SDN 017 Bonra Kab.Polman. The implications of this study were (1) For teachers, the application of a concrete media-based example non-example strategy can improve student learning outcomes. (2) For schools, it can improve the quality of teaching and learning well by using learning strategies